2001
DOI: 10.1159/000052902
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Women with Epilepsy

Abstract: The aim of this study was to analyze the outcome of pregnancy and delivery in epileptic women. A retrospective review of the 41 pregnant women with epilepsy who delivered in the Department of Obstetrics and Perinatology of the University School of Medicine in Lublin over 7 years (1993–1999) was carried out. Women with epilepsy had more pregnancy complications including premature labor, anemia, hypertension, vaginal bleeding, urinary tract infection, nausea and vomiting. An increased risk of congenital malforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…One Class III study 13 also showed an increased risk (p Ͻ 0.05). Another Class III study 8 demonstrated no significant increased risk but was insufficiently sensitive to exclude a substantially increased risk (OR 8.24, 95% CI 0.92-70.32). A Class III study 11 showed no significant increased risk but was not sufficiently sensitive to exclude an increased risk (RR 0.7, 95% CI 0.3-1.4).…”
Section: Premature Contractions and Premature Labor And Deliverymentioning
confidence: 97%
“…One Class III study 13 also showed an increased risk (p Ͻ 0.05). Another Class III study 8 demonstrated no significant increased risk but was insufficiently sensitive to exclude a substantially increased risk (OR 8.24, 95% CI 0.92-70.32). A Class III study 11 showed no significant increased risk but was not sufficiently sensitive to exclude an increased risk (RR 0.7, 95% CI 0.3-1.4).…”
Section: Premature Contractions and Premature Labor And Deliverymentioning
confidence: 97%
“…One Class III study (Wilhelm et al, 1990) also showed an increased risk (p < 0.05). Another Class III study (Laskowska et al, 2001) demonstrated no significant increased risk but was insufficiently sensitive to exclude a substantially increased risk (OR 8.24,. A Class III study (Hiilesmaa et al, 1985) showed no significant increased risk but was not sufficiently sensitive to exclude an increased risk (RR 0.7, 95% CI 0.3-1.4).…”
Section: Premature Contractions and Premature Labor And Deliverymentioning
confidence: 99%
“…Three Class III studies [OR 17.88,.58 (Laskowska et al, 2001); OR 1.58, 95% CI 1.10-2.25 (Olafsson et al, 1998); and OR 2.2, 95% CI 1.42-3.41 (Sawhney et al, 1996) ] demonstrated a significant substantial increased risk.…”
Section: Cesarean Deliverymentioning
confidence: 99%
“…Most of the females with epilepsy have uneventful pregnancies [2,3] but many studies have shown that epilepsy can cause increased complications in the form of abortions, bleeding in early pregnancy, nausea and vomiting, preterm labor, hypertension, intrauterine growth restriction, intrauterine foetal demise and increased caesarean delivery rates [4][5][6]. The fetus is at a much higher risk of teratogenicity due to the antiepileptic drug (AED) intake by the mother [7].…”
Section: Introductionmentioning
confidence: 99%